PENGARUH METODE PROBLEMBASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA : Kuasi Eksperimen pada Mata Pelajaran Ilmu Pengetahuan Sosial Kelas VIII Kompetensi Dasar : Mendeskripsikan Permasalahan Lingkungan Hidup dan Upaya Penanggulangannya Dalam PembangunanBerkelanjutandi SMP Negeri 2 SindangagungKabupaten Kuningan - Rosidi, Idi (2014)
The back ground of this research is based on a real problem i.e. students' low ability to have critical thinking at the eighth grade students of SMP Negeri 2 SindangagungKuningan. It can be seen from answering C4, C5 and C6 questions and the teacher isn't creative in choosing suitable teaching method. Problem based learning is an instructional method that gives students challenge to study for study, to cooperate in group for searching solution of real problem and to prepare students to have critical and analytical thinking.The objective of the research is to know the influence of Problem Based Learning Method towards students' critical thinking ability at the Eighth Grade students' of SMP Negeri 2 SindangagungKuningan.The method used in this reasearch is experimental method with non equivalent group design because it wants to search for the influence of Problem Based Learning Method towards students' critical thinking ability at the Eighth Grade students' of SMP Negeri 2 SindangagungKuningan. This research is carried out at the Eighth Grade students' of SMP Negeri 2 SindangagungKuningan that consists of 5 classes and students' body is 121 students. The sampling technique uses total sampling technique so the population is become sample of this research. The writer divides the sample into 2 groups (experimental and control groups). Experimental group consists of 28 students and control group consists of 29 students. The method of analyzing data uses normality test, homogeneity test and hypothesis test (t-test).The result of this research shows that:Based on statistical testing by using hypothesis test (t-test), the writer gets the data that there is improvement on students' critical thinking after studying by using Problem Based Learning Method with level of significancy (α) is 0.05.The conclusion of this research is:The use of Problem Based Learning can improve students' critical thinking ability. Key words: Problem Based Learning Method, Critical Thinking Penelitianinidilatarbelakangiolehapa yang terjadi di lapanganyaiturendahnya kemampuanberpikirkritissiswakelasVIII di SMP Negeri 2 SindangagungKabupatenKuningan. Hal tersebut terbukti pada pengerjaan soal pada ranah kemampuan c4,c5, dan c6 serta kurang kreatifnya guru dalam memilih metode dalam pembelajaran. Problem Based Learning merupakan metode intruksional yang menantang siswa agar belajar untuk belajar, bekerja sama dalam kelompok untuk mencari solusi bagi masalah yang nyata serta mempersiapkan siswa untuk berpikir kritis dan analitis. DidugapenggunaanmetodeProblem Based Learningakanmempengaruhikemampuanberpikirkrtisisiswa.Tujuanpenelitianiniadalahuntuk mengetahui pengaruh metodeProblem Based Learningterhadapkemampuanberpikirkritis siswa kelasVIII di SMP Negeri 2 SindangagungKabupatenKuningan.Metode yang digunakan dalam penelitian ini adalah metode eksperimen dengan desain non equivalent group design karena penelitian ini adalah berupaya untuk mencari pengaruh penggunaan metodeProblem Based Learningterhadap kemampuan berpikir siswa. Lokasi Penelitian dilaksanakan di SMP Negeri 2 SindangagungKabupatenKuningankelas VIII yang terdiridari5 (lima) kelasdanberjumlah121siswa. Teknik pengambilan sampel dengan total sampling sehingga populasi dijadikan sampel yaitu sebanyak 28 siswa kelas eksperimen dan 29 siswa kelas kontrol.Metodepengolahan data menggunakanujinormalitas, ujihomogenitasdanujihipotesis (uji t). Hasil Penelitian menunjukkan : Berdasarkanpengujianstatistikmenggunakanujihipotesis (uji t) diperoleh data bahwaadanya peningkatan kemampuanberpikirkritissiswasetelah pembelajaran menggunakan metode Problem Based Learning padatarafkepercayaan (α) 0,05. Kesimpulan :PenggunaanmetodepembelajaranberbasismasalahProblem Based Learningdapatmeningkatkankemampuanberpikirkritissiswa. Kata Kunci : Metode Problem Based Learning, Berpikir Kritis